Ionic regulatory strategies of crabs: the transition from water to land - Lucu, Čedomil; Turner, Lucy M. (Frontiers in Physiology, 2024)
Terrestrial crabs (Brachyurans and Anomurans) have invaded land following a variety of pathways from marine and/or via freshwater environments. This switch from water to land requires physiological, ecological, and behavioral adaptations to allow the exploitation of these new environmental conditions. Arguably it is the management of salt and water balance (e.g. osmoregulation) which is integral for their survival and success in an environment where predominantly low saline (e.g. freshwater) water sources are available, sometimes in only minimal amounts. This requires a suite of morphological and biochemical modifications, especially at the branchial chamber of semi-terrestrial and terrestrial crabs to allow the reprocessing of urine to maximize ion uptake. Using knowledge gained from electrophysiology, biochemistry, and more recent molecular biology techniques we present summarized updated models for ion transport for all major taxonomic groups of terrestrial crabs. This is an exciting and fast-moving field of research and we hope this review will stimulate further study. Terrestrial crabs retain their crown as the ideal model group for studying the evolutionary pathways that facilitated the terrestrial invasion.